THE DYNAMICS OF THE PSYCHOLOGICAL PROCESS OF INFORMATION PROCESSING IN SPORT MARKETING - Patruta Teodor (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
Specialist task in marketing communications is different in the case of promotion of products/services that require a high level of consumer involvement in the decision-making process of buying if that consumer involvement is low. In the first case, the emphasis should fall on delivering the most appropriate information, while in the second case, communications must attract attention and make your presence known product, service or brand.Sports marketing in Romania, at the present time, are facing difficulties such as: educational and structural gap, inertia, lack of data, lack of specialised personnel, current status of the athlete, the standard of living. These are all arguments in favour of assuming responsibility by leaders in the field of sport. As is well known, the sport has a dimension of international and global excellence. For the application of marketing marketing plans are needed in the short term, medium and long term marketing programs as well as setting out the contents, sequencing, resources (human, material and financial) and the methods for achieving practical marketing activities. These activities cannot be made without the use of instrumentation research (methods, techniques and tools) and a information marketing system.Because the consumer is the one who assigns meanings to messages received, marketing communications must take account of the differences that may exist between the message intended to be sent by Communicator and the meaning of the message received by the consumer. at the same time, he acquires the marketing concept of its entire economic and social significance at the macro scale. Under these conditions, the Romanian sport and national specificities must follow and stay permanently in accordance with developments in the sport internationally. Sports competition restricted to the local, regional and national loss of significance. This synergy of the sport requires including the adoption of the concept of marketing in the sport organizations, creating organizational structures (by setting up a nucleus, or specialized behavior, Office staffed who possess the skills necessary) and development of marketing strategies, so that it better meets its objectives and performance, but also the wishes of the participant directly or indirectly to the sport. There are two distinct approaches to the manner in which information processing by the consumer and explaining the decision-making process by: • information processing Model-CHIP (Consumer Information Procesiing), in which the consumer is considered an analytical decision-maker, systematic and logical;• Hedonistic or Experiential Approach, in which the consumer's decision is based on feelings, emotions, pleasure or amusement.Of course, you cannot know accurately, nor can I generalize the mental processes that take place in the "black box" of each individual but theories referred to used in marketing, have specific implications for the design of communication strategies, creative strategies and techniques.Having regard to those presented, I think that it is necessary to make a drill down to information processing models applicable to sport.